2012
DOI: 10.1177/0738894211434678
|View full text |Cite
|
Sign up to set email alerts
|

The Interdependence Between Homeland Security Efforts of a State and a Terrorist’s Choice of Attack

Abstract: Consider a state that chooses security levels at two sites (Targets A and B), after which a terrorist chooses which site to attack (and potentially a scope of attack).The state values A more highly. If the state knows which target the terrorist values more highly, he will choose a higher level of security at this site. Under complete information, if the terrorist's only choice is which site to attack, the state will set security levels for which the terrorist prefers to attack A over B if and only if the ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(44 reference statements)
0
4
0
Order By: Relevance
“… 11. Building up the security of a target can lead terrorists to target less-secure assets. For example, research has found that increasing the security of public infrastructure has inadvertently shifted the focus of terrorist attacks towards private individuals, who are less easily secured from these attacks (Brandt and Sandler, 2010; Mathews and Lowenberg, 2012; Santifort et al, 2013). These findings suggest a negative relation between civil conflict and terrorism, if conflict attracts more security and military forces and so shifts terrorist activity away from the conflict.…”
mentioning
confidence: 99%
“… 11. Building up the security of a target can lead terrorists to target less-secure assets. For example, research has found that increasing the security of public infrastructure has inadvertently shifted the focus of terrorist attacks towards private individuals, who are less easily secured from these attacks (Brandt and Sandler, 2010; Mathews and Lowenberg, 2012; Santifort et al, 2013). These findings suggest a negative relation between civil conflict and terrorism, if conflict attracts more security and military forces and so shifts terrorist activity away from the conflict.…”
mentioning
confidence: 99%
“…Jiao and Luo (2018) consider a model in which terrorists and state parties engage in a conflict game that features location choices. In its consideration of location choice by a terrorist party, the study is closely related to issues examined previously by Bier et al (2007) and Mathews and Lowenberg (2012). In the model, three geographically differentiated target locations are assumed where the last location is known only by the terrorist party.…”
Section: Methodologies and Findings Of Articles Included In This Specmentioning
confidence: 99%
“…In 2016, officials at Frontex, EU's border and coast guard agency, admitted that ISIS terrorists are taking advantage of disorganized border checks by posing as migrants to infiltrate Europe. 4 Not surprisingly, as reported by the Pew Research Center, most Europeans fear ISIS terrorist attacks and think that refugees will increase the likelihood of 1 Der Spiegel, 21 Sept., 2015, http://www.spiegel.de/international/germany/refugee-policy-of-chancellor-merkel-divideseurope-a-1053603.html. terrorist attacks in their countries.…”
Section: Introductionmentioning
confidence: 99%
“…It follows from Hausken [2] (2006) that the security efforts of each country are interdependent and can force the terrorist group to optimally determine its target; this is known as the substitution effect. (Such substitution effects have also been identified and analyzed in static, incomplete information environments-see, for example, Bier, Oliveros, and Samuelson [3] (2007) and Mathews and Lowenberg [4] (2012)). Presently, this is considered in the second scenario, in which we assume that there is full awareness by all agents.…”
Section: Introductionmentioning
confidence: 99%